The students gender as a moderating factor of correlation beetween linguistic capital and academic outcomes - Błaszczyński, Kamil (Journal of Education Culture and Society, 2019)
Aim: The aim of this paper was to verify the impact of gender on correlations between native language competences and academic activity of master grade students of social sciences in Poland. Results are disscussed with other international findings. Methods: Gathering of the data was used via auditorial survey. Data was collected from 235 students (163 female, 73 male) from one of polish national universities on faculty of social sciences. Data has been analysed using T-Students test and Linear Regression models. Results: T-Students test results indicated that female students had significantly higher education outcomes and study results scores than male students. Regression analysis revealed that gender as a moderating factor of linguistic capital was a significant predictor in regard to students education outcomes and study results. The main part of linguistic capital significantly moderated by gender were language experiences, regarded toward study results scores. Conclusions: Female students have equall linguistic capital and language experiencess as male students, althoug they are more capable in using that capitale for their benefit in the context of academic education. Implication of the study and future recommendation are advised.